Goliath - Westerfeld, Scott; Thompson, Keith, 1982- (New York : Simon Pulse, 2012)
Alek and Deryn encounter obstacles on the last leg of their round-the-world quest to end World War I, reclaim Alek's throne as prince of Austria, and finally fall in love.
Sequel to: Behemoth.
School Library Journal, September 2011
Horn Book, November 2011
Kirkus Review, August 2011
Young Adult
Keywords: Animals, Mythical -- Juvenile fiction; Princes -- Juvenile fiction; Genetic engineering -- Juvenile fiction; Imaginary creatures -- Fiction; Princes -- Fiction; War -- Fiction; Genetic engineering -- Fiction; Science fiction; Imaginary creatures -- Fiction; Mythical animals -- Fiction; Princes -- Fiction; War stories; Genetic engineering -- Fiction; Science fiction; War stories; Science fiction